Approximation of systems with delay their stability - Cherevko, Ihor; Tuzyk, Iryna (Masaryk University, Brno, Czech Republic, 2022)
In this paper, the schemes of approximation of linear systems with delays by special systems of ordinary differential equations are considered and the connections between their solutions are investigated. This allowed us to build algorithms for studying the stability of linear systems with delay.